Theoretical principle and design of high-imaging-quality refractive-diffractive optical elements by multifocal-simultaneous aberration-correction method - Bo Dong; Ying Yang; Changxi Xue (Results in Physics, 2024)
Multifocal refractive-diffractive optical elements, which produce arbitrary light distribution, are widely used in lightweight and compact optical systems. However, due to the lack of research on the diffraction aberration principle for multifocal refractive-diffractive optical elements, the construction of refractive-diffractive multifocal aberration system and the theoretical model of simultaneous aberration-correction for multi-focus have not been built. For the first time, we proposed a physics model named multifocal-simultaneous aberration-correction (MSAC) for refractive-diffractive optical elements to achieve balance aberration correction at multifocal points at the same time. First, we derived the expression of diffraction aberration principle for refractive-diffractive optical elements. Then, through four steps, we give the whole established process of MSAC model. Through the multifocal diffractive intraocular lens (IOL) which usually used multifocal refractive-diffractive optical element, we showed the application and the solution process of MSAC model in optical system. Finally, an aberration-correction multifocal intraocular example was optimized and discussed. The results showed that the MSAC model can realize the aberration-correction balance design at multiple focus. The proposed model can be applied to the design of multifocal refractive-diffractive optical elements.